EMPOWERMENT OF FISH FARMING GROUPS THROUGH DIVERSIFICATION OF FISH PROCESSED PRODUCTS TO IMPROVE THE WELFARE OF FARMERS IN NGRAJEG VILLAGE MUNGKID SUB-DISTRICT OF MAGELANG - Murwatiningsih, Murwatiningsih; Oktarina, Nina; Widodo, Joko (Indonesian Journal of Devotion and Empowerment, 2020)
Fish commodity at the time of harvest in Ngrajeg village of Magelang Regency, the price becomes falling and fish that do not sell is also easy to rot. This condition will harm fish farmers. Therefore, it is necessary to diversify fish processed products to increase the economic value of fish. However, conditions in the field show that fish farmers in Ngrajeg are still limited in their knowledge and skills related to diversification of fish products. This community service activity aims to provide science stimulus to fish farmers regarding the diversification of processed fish products into a variety of economically valuable products. The target audience of this activity is the fish farmers in Ngrajeg village of Mungkid Magelang Sub-District. The methods used in problem solving through training in the form of material and practice. Hopefully after the fish farmers increase their knowledge about diversification of processed fish products can apply it. So the income of fish farmers will increase and ultimately the welfare of fish farmers will also increase. Komoditi ikan pada saat panen raya di desa Ngrajeg Kabupaten Magelang, harganya menjadi jatuh dan ikan yang tidak laku juga mudah busuk. Kondisi ini akan merugikan petani ikan. Oleh karena itu perlu dilakukan diversifikasi produk olahan ikan untuk meningkatkan nilai ekonomis dari ikan. Akan tetapi kondisi di lapangan menunjukkan para petani ikan di Ngrajeg masih terbatas pengetahuan dan keterampilannya terkait dengan diversifikasi produk olahan ikan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan stimulus ilmu pengetahuan kepada para petani ikan mengenai diversifikasi produk olahan ikan menjadi aneka produk bernilai ekonomis. Khalayak sasaran dari kegiatan ini adalah para petani ikan di desa Ngrajeg Kecamatan Mungkid Magelang. Adapun metode yang digunakan dalam pemecahan masalah melalui pelatihan dalam bentuk pemberian materi dan praktek. Harapannya setelah para petani ikan bertambah pengetahuannya tentang diversifikasi produk olahan ikan dapat menerapkannya. Sehingga pendapatan petani ikan akan meningkat dan pada akhirnya kesejahteraan petani ikan juga meningkat.